Effectiveness of the Flipped Classroom in Health Sciences University Programs: A Literature Review - Nocetti-García, Diego; Auad-Brito, Maura; Henriquez-Villarroel, David (Universidad y Salud, 2023)
Introduction: Higher education institutions have implemented active learning approaches, such as the Flipped Classroom, to promote the education of their students. Nevertheless, there is conflicting evidence regarding the benefits derived from its implementation. Objective: To determine the effectiveness of the Flipped Classroom application in the education of university students from Health Sciences undergraduate programs. Materials and methods: A systematized narrative review of the literature published between 2012 and 2022. Pubmed, SciELo, Scopus y Web of Science were used as sources of primary articles. A revised version of the Kirkpatrick model was used to assess the effectiveness of the Flipped Classroom. Results: 34 out of the 1020 retrieved articles reached the quantitative synthesis phase. Students value positively this didactic model and acknowledge its contributions in the development of attitudes, knowledge and skills. In contrast, some studies show an increase in the workload and stress levels of students. Conclusions: The evidence suggests that Flipped Classroom is a valid didactic model for the education of Health Sciences students. Future studies should consider the effectiveness of its implementation at a long term organizational level.